The relationship between computers - based multimedia technology and the development of the English listening competence in the case of the Advanced Intensive English I semester II-2012 students at the Foreign Language Department in the University of El Salvador - Hernández López, Ericka Guadalupe; Hernández Mauricio, Wendy Lissette; Ramírez Mendoza, José Salvador; Oliva José Israel; Ayala, Edgar Nicolás (San Salvador, El Salvador : Universidad de El Salvador, 2013)
The technological era, it is now called in TV programs; when talking about all the new techniques that have appeared to practice the listening skill by using devices and technologies that are emerging day after day. The Foreign Language Department is not an exception to the exposition to these technologies, however not all the students have the same perception about the technological era. The most important aspect of the new technology is that it gives more benefits to the students because of the multimedia capacity that it has, as it is shown in the Cognitive Theory of Multimedia by Mayer; in here is where it has to determine if in fact multimedia works in teaching at Foreign Language Department the same way as it works in different countries. Knowing that the listening skill competence is one of the most difficult skills to develop, in this research it is needed to take into account three main factors, before stating that multimedia has a direct impact on the listening skill; the first one is that multimedia is related to the students particular interests, followed by the evidence that the successfully use of multimedia enhances the development of the listening competence and at last it is understood that due to the content shown to the students, these ones react positively to the exposure of authentic material by using multimedia technology. These factors contribute to the explanation on how the multimedia helps to improve their listening comprehension skill. A very important aspect of the modern technology is the multimedia resources that are being used in our academic environment for developing the students’ listening competence, but what does it mean exactly by multimedia? According to some researchers like Richard Mayer defines multimedia as the presentation of material, ii containing words and pictures; some other writers mention that multimedia is when you use images and sounds combined in order to enhance a specific content. In this research the term multimedia is going to be understood as a presentation containing audio and video, such type of multimedia can be found in in different presentations or with concepts that understand as multimedia a power point presentation, however it is called multimedia only to the material presented with audio and video simultaneously through a computer- based software.
Incluye anexos.
bibliografia : hojas 49
Texto en Inglés
Keywords: Inglés -- Enseñanza